Hubungan Pengetahuan Tentang Vaksin Covid-19 dengan Tingkat Kecemasan Orang Tua yang Anaknya Menerima Vaksin di Wilayah Kerja UPT Puskesmas Kereng Bangkirai: Correlation of Knowledge about Covid-19 Vaccine with Anxiety Level of Parents Which Children Received Vaccine in The Work Area of UPT Puskesmas Kereng - Andriani, Susi; Ningsih, Fitriani; Ovany, Riska (Jurnal Surya Medika (JSM), 2023)
COVID-19 is a disease caused by the corona virus that attacks the respiratory tract, causing high fever, cough, flu, shortness of breath and sore throat. Addressing widespread hesitation about receiving a COVID-19 vaccine requires the collaborative efforts of governments, health policy makers and media sources, including recommended social media to build confidence in COVID-19 vaccination among the general public, through timely dissemination of messages and This is very clear through trusted advocacy channels on the safety and efficacy of currently available COVID-19 vaccines. In addition, the role of health workers must be increased in providing health promotion about vaccination so that the public can know that the benefits of vaccination outweigh the side effects. The purpose of this study was to determine the relationship between knowledge about the COVID-19 vaccine and the level of anxiety of parents whose children received the vaccine. The design of this study used analytical research methods using a cross sectional design. The population in this study were all parents whose children received vaccines in the working area of ​​the UPT Puskesmas Kereng Bangkirai with a total sample of 52 respondents. The sampling method used is purposive sampling. The research data was taken using a questionnaire after tabulating the existing data and analyzed using the chi square test. The results showed that there was a relationship between knowledge about the COVID-19 vaccine and the level of anxiety of parents whose children received vaccines in the working area of ​​the UPT Puskesmas Kereng Bangkirai (with a P value of 0.004 < a 0.05). UPT Puskesmas Kereng Bangkirai needs to make programs and policies related to activities vaccination, then involving Public Health Workers to provide optimal health promotion in many promotive aspects so that knowledge gets better.